2009 IEEE International Workshop on Multimedia Signal Processing 2009
DOI: 10.1109/mmsp.2009.5293277
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual similarity metrics for retrieval of natural textures

Abstract: Abstract-We investigate perceptual similarity metrics for the content-based retrieval of natural textures. The goal is to find perceptually similar textures that may have significant differences on a point-by-point basis. The evaluation of such metrics typically requires extensive and cumbersome subjective tests. The focus of this paper is on the recovery of textures that are "identical" to the query texture, in the sense that they are pieces of the same texture. This is important in content-based image retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…46 and precision-recall plots 47 are also commonly used. Zujovic et al 32 performed extensive experiments for this type of application, using nearly 280,000 pairs of texture images, to assess the performance of their metric to the well known SSIM and CW-SSIM metrics, and demonstrated that it offers considerable advantages.…”
Section: Content-based Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…46 and precision-recall plots 47 are also commonly used. Zujovic et al 32 performed extensive experiments for this type of application, using nearly 280,000 pairs of texture images, to assess the performance of their metric to the well known SSIM and CW-SSIM metrics, and demonstrated that it offers considerable advantages.…”
Section: Content-based Retrievalmentioning
confidence: 99%
“…32. The conclusion was that STSIM-2 performs best, with 77.2% success in retrieving the correct document as the first returned result (precision at one), whereas for PSNR this happens only for 6% of the images.…”
mentioning
confidence: 95%
“…For example, in [4], the focus was on the recovery of textures that are "identical" to the query texture, in the sense that they are pieces of the same texture. All that is needed in this case is to start with a database consisting of perceptually uniform textures, which we can then cut into (perhaps partially overlapping) pieces, in order to obtain the test database.…”
Section: Introductionmentioning
confidence: 99%
“…In the information retrieval community this known as the known-item search [5]. Common measures for this type of retrieval systems include precision at one (measures in how many cases the first retrieved document is relevant), mean reciprocal rank (measures how far away from the first retrieved document is the first relevant one), mean average precision and precision-recall plots [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation